Valuing technology: A qualitative interview study with physicians about insulin pump therapy for children with type 1 diabetes. Issue 1 (January 2016) - Shulman, Rayzel; Miller, Fiona A.; Daneman, Denis; Guttmann, Astrid
Highlights: We examine how physicians value insulin pump therapy for children with diabetes. Physicians recognize limitations of pump therapy but nonetheless see its value. Pumps are valued as new technologies and in the therapeutic relationship. Funding decisions and diffusion processes are mediated by value judgments. Understanding how technologies are valued can inform policy processes. Abstract: Insulin pumps for children with type 1 diabetes have been broadly adopted despite equivocal evidence about comparative effectiveness. To understand why and inform policy related to public funding for new technologies, we explored how physicians interpret the value of pumps. We conducted open-ended, semi-structured interviews with 16 physicians from a pediatric diabetes network in Ontario, Canada, and analyzed the data using interpretive description. Respondents recognized that pumps fell short of expectations because they required hard work, as well as family and school support. Yet, pumps were valued for their status as new technologies and as a promising step in developing future technology. In addition, they were valued for their role within a therapeutic relationship, given the context of chronic childhood disease. These findings identify the types of beliefs that influence the adoption and diffusion of technologies. Some beliefs bear on hopes for new technology that may inappropriately hasten adoption, creating excess cost with little benefit. On the other hand, some beliefs identify potential benefits that are not captured in effectiveness studies, but may warrant consideration in resource allocation decisions. Still others suggest the need for remediation, such as those bearing on disparity in pump use by socioeconomic status. Understanding how technologies are valued can help stakeholders decide how to address such beliefs and expectations in funding decisions and implementation protocols.